Potential applications of ferulic acid from natural sources - Kumar, Naresh; Pruthi, Vikas (Biotechnology reports (Amsterdam, Netherlands), 2014)
Ferulic acid (FA), a ubiquitous natural phenolic phytochemical present in seeds, leaves, bothin its free form and covalently conjugated to the plant cell wall polysaccharides, glycoproteins,polyamines, lignin and hydroxy fatty acids. FA plays a vital role in providing the rigidity to the cell wall and formation of other important organic compounds like coniferyl alcohol, vanillin, sinapic, diferulic acid and curcumin. FA exhibits wide variety of biological activities such as antioxidant, antiinflammatory, antimicrobial, antiallergic, hepatoprotective, anticarcinogenic, antithrombotic, increase sperm viability, antiviral and vasodilatory actions, metal chelation, modulation of enzyme activity, activation of transcriptional factors, gene expression and signal transduction.